1995
DOI: 10.1159/000119226
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Carnitine in Chronic Fatigue Syndrome: Clinical Correlates

Abstract: Carnitine is essential for mitochondrial energy production. Disturbance in mitochondrial function may contribute to or cause the fatigue seen in chronic fatigue syndrome (CFS) patients. One previous investigation has reported decreased acylcarnitine levels in 38 CFS patients. We investigated 35 CFS patients (27 females and 8 males); our results indicate that CFS patients have statistically significantly lower serum total carnitine, free carnitine and acylcarnitine levels, not only lower acylcarnitine levels as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 10 publications
5
34
0
Order By: Relevance
“…Correlations between lower acylcamitine levels and worse clinical CFS symptomatology has been previously reported [12], Likewise, in a previous study, we reported decreased free and total carnitine serum levels being cor related with CFS symptomatology [13]. In the current treatment program we found decreased free carnitine lev els to be associated with the female sex, an observation that is well established in normals [32,33], Also, we found decreased acylcamitine levels to be associated with dis ease severity in two study psychometric parameters used, thus confirming previously reported results [12], Higher acylcamitine and total carnitine levels were also associat ed with longer duration of illness and with chronic onset of illness, observations that have not been previously reported.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Correlations between lower acylcamitine levels and worse clinical CFS symptomatology has been previously reported [12], Likewise, in a previous study, we reported decreased free and total carnitine serum levels being cor related with CFS symptomatology [13]. In the current treatment program we found decreased free carnitine lev els to be associated with the female sex, an observation that is well established in normals [32,33], Also, we found decreased acylcamitine levels to be associated with dis ease severity in two study psychometric parameters used, thus confirming previously reported results [12], Higher acylcamitine and total carnitine levels were also associat ed with longer duration of illness and with chronic onset of illness, observations that have not been previously reported.…”
Section: Discussionsupporting
confidence: 86%
“…Also, clinical correlations were noted between increases in acyl carnitine levels and improvement in fatigue symptoms [12]. We have found decreased total carnitine, free carni tine and acylcarnitine levels in 35 CFS patients (27 females and 8 males) [13]. We have also found a statisti cally significant correlation between serum levels of total and free carnitine and clinical symptomatology [13].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…A primary genetic carnitine deficiency occurs in children with dilated cardiomyopathy, hypoglycemia, and low carnitine contents in plasma, liver and muscle, owing to a defect in a common high-affinity trans- Matsumoto/Sato/Ohashi/Araki/Tadokoro/ Osumi/Ito/Morita/Amano port system [21][22][23]. Acquired forms of carnitine deficiency are observed in women during pregnancy [24], patients receiving long-term total parenteral nutrition [25], patients with chronic fatigue syndrome [26,27], and chronic HD patients. HD is of particular note because it induces a substantial loss of carnitine from the skeletal and cardiac muscle.…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports have described patients labeled with chronic fatigue syndrome (CFS) ultimately diagnosed with an energy metabolism disorder, based on measured deficiencies in respiratory chain or fatty acid oxidation enzymes, or on the basis of carnitine deficiency [88][89][90]. Although beyond the scope of this article, these earlier findings resulted in considerable interest among clinicians and patients to perform in-depth evaluations of those suffering with CFS.…”
Section: Chronic Fatiguementioning
confidence: 99%